Structural and electronic properties of highly doped topological insulator Bi2Se3 crystals. Issue 1 (6th December 2012) - Cao, Helin; Xu, Suyang; Miotkowski, Ireneusz; Tian, Jifa; Pandey, Deepak; Hasan, M. Zahid; Chen, Yong P.
Abstract <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text> We present a study of the structural and electronic properties of highly doped topological insulator Bi2Se3 single crystals synthesized by the Bridgman method. Lattice structural characterizations by X‐ray diffraction, scanning tunneling microscopy, and Raman spectroscopy confirmed the high quality of the as‐grown single crystals. The topological surface states in the electronic band structure were directly re‐ vealed by angle‐resolved photoemission spectroscopy. Transport measurements showed that the conduction was dominated by the bulk carriers and confirmed a previously observed bulk quantum Hall effect in such highly doped Bi2Se3 samples. We briefly discuss several possible strategies of reducing bulk conductance. (© 2013 WILEY‐VCH Verlag GmbH & Co. KGaA, Weinheim)